Neurosteroids: oligodendrocyte mitochondria convert cholesterol to pregnenolone. - Hu, Z Y (1987)
Oligodendrocyte mitochondria from 21-day-old Sprague-Dawley male rats were incubated with 100 nM [3H]cholesterol. It yielded [3H]pregnenolone at a rate of 2.5 +/- 0.7 and 5-[3H]pregnene-3 beta, 20 alpha-diol at a rate of 2.5 +/- 1.1 pmol per mg of protein per hr. Cultures of glial cells from 19- to 21-day-old fetuses (a mixed population of astrocytes and oligodendrocytes) were incubated for 24 hr with [3H]mevalonolactone. [3H]Cholesterol, [3H]pregnenolone, and 5-[3H]pregnene-3 beta, 20 alpha-diol were characterized in cellular extracts. The formation of the 3H-labeled steroids was increased by dibutyryl cAMP (0.2 mM) added to the culture medium. The active cholesterol side-chain cleavage mechanism, recently suggested immunohistochemically and already observed in cultures of C6 glioma cells, reinforces the concept of "neurosteroids" applied to delta 5-3 beta-hydroxysteroids previously isolated from brain.